Pelatihan Penyusunan Perangkat Pembelajaran Sains Inovatif berbasis Deep Learning bagi Guru SMP/ MTs Kabupaten Tuban - Rosdiana, Laily; Hariyono, Eko; Budiyanto, Mohammad; Nabilah, Hasna (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2026)
Training in developing innovative science learning tools is considered very important, especially for science teachers in Tuban. One of the training methods is introducing innovative science learning tools based on deep learning, an in-depth learning approach that emphasizes strengthening student engagement in the learning process through contextual, meaningful, and enjoyable activities (mindful, meaningful, and joyful learning). This is a new trend in Science Education, so that the resulting learning products can be adapted and utilized by the community. The training focuses on science teachers in Tuban. The stages of this activity include 1) the preparation stage; 2) the material presentation stage; 3) the mentoring stage; and 4) the evaluation stage. These stages are carried out to support the implementation of the training in providing an in-depth understanding of deep learning and providing guidance to teachers regarding product creation. A solution that can be offered to these problems is by conducting training in developing innovative science learning tools based on deep learning. Technical support and mentoring can also be provided during and after the training to ensure the mentoring runs smoothly and successfully. The resulting product is an innovative science learning tool based on deep learning according to the material identified and the problems that teachers want to solve.